2005
DOI: 10.1097/01.aog.0000168441.79050.03
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adiponectin Concentration in Early Pregnancy and Subsequent Risk of Hypertensive Disorders

Abstract: Our findings suggest a strong association between hypoadiponectinemia and the risk of hypertensive disorders in pregnancy, especially with preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 17 publications
4
44
0
7
Order By: Relevance
“…23,24 As a vasoactive substance reacting with its specific receptors (AdipoR1 and AdipoR2), adiponectin has important physiological roles, such as protecting vascular endothelial cells, increasing insulin sensitivity, inhibiting inflammation and inhibiting atherosclerosis. By measuring plasma adiponectin in 1842 pregnant women in early pregnancy and tracking the outcomes of their pregnancies, D'Anna et al 4 found that plasma adiponectin in patients with preeclampsia was lower than in pregnancy-induced hypertension patients and normal patients. Ramsay et al 25,26 also found that plasma adiponectin was significantly higher in preeclampsia compared with normal controls, although the adiponectin level was unrelated to adiponectin mRNA expression in the placenta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 As a vasoactive substance reacting with its specific receptors (AdipoR1 and AdipoR2), adiponectin has important physiological roles, such as protecting vascular endothelial cells, increasing insulin sensitivity, inhibiting inflammation and inhibiting atherosclerosis. By measuring plasma adiponectin in 1842 pregnant women in early pregnancy and tracking the outcomes of their pregnancies, D'Anna et al 4 found that plasma adiponectin in patients with preeclampsia was lower than in pregnancy-induced hypertension patients and normal patients. Ramsay et al 25,26 also found that plasma adiponectin was significantly higher in preeclampsia compared with normal controls, although the adiponectin level was unrelated to adiponectin mRNA expression in the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…1 The prevention and management of preeclampsia are difficult, especially in severe cases, because the etiology and pathogenesis of preeclampsia are unclear. Recent studies indicate that the interaction of adiponectin and its receptors might have a considerable role in the pathogenesis of preeclampsia [2][3][4] because of their important physiological functions, including anti-inflammatory, anti-atherosclerotic, vascular endothelial cell protection and insulin-sensitizing effects. [5][6][7][8] Numerous single-nucleotide polymorphisms (SNPs) exist in the human adiponectin gene, located on chromosome 3q27.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal (34,78) and cord (79) leptin concentrations may be elevated in preeclampsia. Adiponectin, a hormone associated with increased insulin sensitivity, is elevated in the maternal circulation late in preeclamptic compared with normal pregnancies (78); however, levels early in pregnancy may be reduced (80). The association of preeclampsia with maternal third-trimester levels of resistin, a hormone possibly involved in insulin resistance and inflammation, is equivocal (78,81).…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 99%
“…Since low concentrations of adiponectin are associated with obesity, insulin resistance, Type 2 diabetes, hypertension [47] and obesity-related malignancies, a possible role has been hypothesized in the pathogenesis of PE. However, its role has not yet been well defined, as contrasting results have been found [48,49].…”
Section: Prognostic Toolsmentioning
confidence: 99%